Rich Representations of Visual Content for Screen Reader Users - Morris, Meredith Ringel; Johnson, Jazette; Bennett, Cynthia; Cutrell, Ed (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
Alt text (short for “alternative text”) is descriptive text associated with an image in HTML and other document formats. Screen reader technologies speak the alt text aloud to people who are visually impaired. Introduced with HTML 2.0 in 1995, the alt attribute has not evolved despite significant changes in technology over the past two decades. In light of the expanding volume, purpose, and importance of digital imagery, we reflect on how alt text could be supplemented to offer a richer experience of visual content to screen reader users. Our contributions include articulating the design space of representations of visual content for screen reader users, prototypes illustrating several points within this design space, and evaluations of several of these new image representations with people who are blind. We close by discussing the implications of our taxonomy, prototypes, and user study findings.